Hepatitis B virus infection and ABO/Rh blood groups - Genc, Ozlem (International Journal of Research in Medical Sciences, 2017)
Background: Chronic HBV infection is a significant public health problem all around the world. It is not clear if ABO/Rh blood groups have a role in the development of chronic forms of hepatitis B virus (HBV) infection. The aim of the study was to investigate the relationship between chronic HBV infection and ABO/Rh blood groups. Methods: The study was designed as a retrospective study that included totaled 937 individuals: 453 patients diagnosed with chronic hepatitis and 484 healthy individuals as the control group. HBsAg (hepatitis B surface antigen) and blood groups results of patients between the years 2013-2015 were collected by reviewing the laboratory results. During these three years HBsAg was performed on the architect i2000sr (Abbott diagnostic, Illinois, USA) with ELISA and ABO/Rh blood groups were analyzed with gel centrifugation method (Grifols, Barcelona, Spain). Results: Blood group A Rh positive was higher than other blood types in the chronic hepatitis B group (44.3%) and in control group (41.9%), whereas blood types O, AB, and B were similar between cases with chronic hepatitis and controls (p>0.05). HBV infection was moderately less frequent in subjects with AB positive blood group (p=0.07). The prevalence of Rh positive was 89.1% in patients and 88.2% in the control group (p>0.05). Conclusions: This study showed that there was not an association between ABO/Rh blood groups and chronic HBV infection, but there is a need for different and more numerous case-control studies about this subject.